Grade 1 Solo Pan Exam is Here - Unknown (Trinidad Express)
The first graded examinations in solo pan performance will be held in April 1995. Coordinated by Dr. Anne Osborne, the committee included members from the Creative Arts Centre, Faculty of Arts and General Studies, UWI and others from Pan Trinbago.
Keywords: Steel bands (Music) -- Development -- Trinidad and Tobago; Music -- Examinations, questions, etc.; Music -- Instruction and study -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago